Bacterial Contamination and Decontamination of Cryopreserved Freshwater Fish Milt in Thailand: Case Study of Silver Barb (Barbodes gonionotus) Milt - Ninkoson, Chayapa; Sooksawat, Treerat; Boonthai, Traimat; Vuthiphandchai, Verapong; Nimrat, Subuntith (Science Essence Journal, 2019)
บทคัดย่อ การปนเปื้อนแบคทีเรียเป็นสาเหตุสำคัญที่ทำให้คุณภาพน้ำเชื้อลดลงและสร้างความกังวลต่อความปลอดภัยทางชีวภาพของน้ำเชื้อแช่แข็ง การปนเปื้อนแบคทีเรียในการแช่แข็งน้ำเชื้อเกิดขึ้นได้ในทุกขั้นตอน โดยเฉพาะอย่างยิ่งขั้นตอนการเก็บรวบรวมน้ำเชื้อ การปนเปื้อนแบคทีเรียส่วนใหญ่มักปนเปื้อนจากน้ำที่ใช้เลี้ยงปลา ครีบก้น และอุจจาระและปัสสาวะของปลา การปฏิบัติตามแนวทางของการปฏิบัติงานที่ถูกสุขอนามัยสำหรับห้องปฏิบัติการสามารถลดการปนเปื้อนแบคทีเรียได้ นอกจากนี้การเก็บรวบรวมน้ำเชื้อโดยการใช้สายสวนร่วมกับการล้างช่องเพศปลาด้วยน้ำปราศจากเชื้อและเช็ดบริเวณช่องเพศให้แห้ง และการไม่นำน้ำเชื้อที่ปนเปื้อนอุจจาระและปัสสาวะมาใช้ในการแช่แข็งยังช่วยลดปริมาณและชนิดของแบคทีเรียในน้ำเชื้อได้อย่างมาก การประยุกต์ใช้ยาปฏิชีวนะผสม 0.25% Penicillin-Streptomycin ในน้ำเชื้อเป็นอีกทางเลือกหนึ่งในการลดการปนเปื้อนแบคทีเรียในน้ำเชื้อแช่แข็งโดยไม่ส่งผลกระทบต่อคุณภาพสเปิร์มและการปฏิสนธิ อย่างไรก็ตามแบคทีเรียก่อโรคบางชนิด ได้แก่ Aeromonas hydrophila subsp. hydrophila และ Pseudomonas fluorescens ยังคงพบได้และดื้อต่อยาปฏิชีวนะผสมทั้งสองชนิดนี้ รวมทั้งสามารถถ่ายทอดจากน้ำเชื้อแช่แข็งไปยังตัวอ่อนของปลาตะเพียนขาวที่เกิดจากการผสมเทียม ดังนั้นควรทำการศึกษาวิจัยเพื่อพัฒนาเทคโนโลยีใหม่ๆ ที่มีประสิทธิภาพในการลดการปนเปื้อนแบคทีเรียก่อโรคในน้ำเชื้อแช่แข็งโดยไม่ส่งผลกระทบต่อคุณภาพน้ำเชื้อต่อไป คำสำคัญ: ปลาตะเพียนขาว แบคทีเรีย การปนเปื้อน น้ำเชื้อแช่แข็ง ABSTRACT Bacteria contamination is an important factor of decline in milt quality and creates a concern in biological safety of cryopreserved sperm. Bacterial contamination can occur in every step of cryopreservation processes, particularly, during milt collection. Most contaminated bacteria usually originate from culture water, anal fins, and fecal and urine mixtures. Implementation of a standard sanitation protocol required for minimal bacterial contamination in laboratory is capable of decreasing degree of contamination. Moreover, rinsing urogenital aperture with sterile water and drying urogenital opening prior to milt collection using a catheter, and no use of milt with fecal and urine mixture can dramatically reduce the number and type of bacterial contaminants in cryostored milt. Application of 0.25% penicillin-streptomycin mixture is also an alternative technique for minimizing bacteria contaminants in cryopreserved milt without negative effect on sperm quality and fertilization success. However, some pathogenic bacteria e.g. Aeromonas hydrophila subsp. hydrophila and Pseudomonas fluorescens still remain due to their resistance to these mixed antibiotics and they can be transferred from cryostored milt to artificially inseminated embryos of silver barb. Therefore, development of effective novel technology for decontamination of pathogenic bacteria in cryostored milt without detrimental effect on fish sperm should be further established. Keywords: silver barb, bacteria, contamination, cryopreserved milt